Efforts to Prevent Deviant Behavior in Identity and Sexual Orientation through Interactive Talk Show and Social Campaign in the Campus Environment - Dwi Novrianda; Randy Refnandes; Agus Sribanowo; Fitri Mailani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Limited understanding regarding healthy relationships, religious implications, the impact of LGBTQ occurrences, psychological susceptibilities associated with LGBTQ, and inappropriate approaches towards LGBTQ individuals can heighten one's susceptibility towards developing LGBTQ tendencies or mental disorders. This initiative, referred to as IbDM, will be executed with the utilization of a social campaign approach and interactive talk shows, to cultivate positive awareness and effective strategies for addressing and preventing the rise in LGBTQ transmission. The social campaign involve distributing pamphlets and pocketbooks about LGBTQ matters across all faculties in Unand, serving as a reminder and platform for introspection in anticipation of LGBTQ transmission. Additionally, incorporating interactive and captivating talk show activities featuring knowledgeable speakers will enable the dissemination of understanding, thereby enhancing the academic community's awareness in a more profound manner. The content presented during these activities will encompass various aspects of LGBTQ, including social and religious dimensions, cultural and legal considerations, and health-related perspectives. This activity has provided an overview of the perceptions of students involved as participants regarding LGBTQ behaviour. All participants (100%) view LGBTQ as deviant behavior, the importance of the role of parents in building children's character and identity, and the large influence of the social environment as a barrier to LGBTQ. Therefore, it is important for the role of policymakers at the central and regional government levels, leaders of higher education institutions, the academic community, health practitioners, and other fields to be able to work together in enforcing strict legal regulations against LGBTQ, socializing the impact of sexual identity and orientation deviation, strengthening the role parents and social environment as deterrents to deviant sexual identity and orientation behavior.